Role of Lone Pair of Electron in the Polarisation Behaviour of Aluminium in Dimethylamine Role of Lone Pair of Electron in the Polarisation Behaviour of Aluminium in Dimethylamine - Yadav, P.N.S. (Asian Journal of Chemistry, 2010)
The polarization behaviour of 1100 and 3003 aluminium in aqueous solution of dimethylamine has been carried out using potentiostatic methods to explore the role of lone pair of electrons of nitrogen atom. Active-passive nature of the anodic curves has been has been investigated in the concentration range from 2 to 0.1% dimethylamine. By decreasing its concentration both anodic and cathodic polarisation curves have been shifted towards lower region of current density. But critical current density decreases wheras steady state corrosion potential and primary potential generally increase.